Heart rate and its variability in agility dogs at high altitude - Vargas-Pinto, Pedro (2017)
The aim of this study was to determine the effect of the practice of dog Agility in high altitude (2550 m above the sea level) on heart rate and its variability. Ten Agility Border Collie dogs (Agility group) and ten sedentary Border Collie dogs (Sedentary group) were evaluated by electrocardiogram at baseline, warm-up, sub-maximal exercise (maximum speed of 5 km/h for 3 min) and rest in an electric treadmill. Heart rate was compared for all time points among groups. Heart rate variability was compared by frequency domain for baseline and at rest. The Agility group had lower heart rates at all time points (p<0.05) except at the beginning of the rest period. The agility group showed higher high frequency components at baseline and rest (p<0.05).